Enhancement of Cobalt Concentration Supported on Mesoporous Silica towards the Characteristics and Activities of Catalysts for the Conversion of Waste Coconut Oil into Gasoline and Diesel Oil - Wega Trisunaryanti; Triyono Triyono; Nugroho Raka Santoso; Savitri Larasati; Cahyarani Paramesti; Dyah Ayu Fatmawati (Universitas Gadjah Mada, 2021)
The analysis of the effect of cobalt concentration supported on mesoporous silica (MS) has been evaluated. This study was aimed to observe the physical and chemical characteristics of the catalysts, and also to study the catalytic activity and its selectivity towards gasoline and diesel oil products in the hydrocracking process of waste coconut oil. The MS was produced using Lapindo mud, where the CTAB was used as the mesopore templating agent. The Co/MS catalyst was prepared by the wet impregnation method with various concentrations of Co. The characterization of the catalyst includes silica purity test by XRF, determination of Co content by AAS, the crystallinity by XRD, the catalyst porosity by SAA, physical pore structure by SEM and TEM, and total acidity by the gravimetric method using NH3 base vapor adsorption. The hydrocracking was carried out in a hydrocracking reactor using various concentrations of Co/MS catalysts with the ratio of catalyst/feed = 1/50. The products of the hydrocracking process were liquid, coke, and gas. The composition of the hydrocracking liquid products was analyzed by GC-MS. Based on the results of the catalytic activity test, it was concluded that the Co(1)/MS catalyst, which had the highest acidity, showed the best catalyst selectivity towards gasoline and diesel fractions.